Relationship between coping, anxiety and depression among a Mexican sample during the onset of the Covid-19 pandemic - Mestas, Lilia; Gordillo, Fernando; Cardoso, Marco Antonio; Arana, José M.; Pérez, Miguel Ángel; Colin, Diana Laura (Revista de Psicopatología y Psicología Clínica, 2021)
Abstract: The coping strategies used during the COVID-19 pandemic could explain why certain individuals experience higher levels of anxiety and depression than others. A sample of 747 subjects completed an ad-hoc questionnaire on their habits during the pandemic, the Stress Coping Questionnaire (SCQ) focused on COVID-19; the Beck Anxiety Inventory (BAI) and the Beck Depression Inventory (BDI). High percentages of the sample recorded moderate and severe levels of anxiety (45.38%) and depression (32.13%), which were higher in women. The regression model explained 30.8% and 33.5% of the variance in anxiety and depression, respectively, with the predictive capacity being greater for women than men. Passive coping strategies made up the regression model, with negative self-targeting having the greatest predictive capacity for both anxiety (R2 = 0.204) and depression (R2 = 0.215). The results reveal the need to work on reinforcing the perception of control over the situation, promoting active coping strategies. Keywords: Emergency; stress; gender; habits; pandemic. Relaciones entre el afrontamiento, la ansiedad y la depresión en una muestra mexicana durante el inicio de la pandemia de COVID-19 Resumen: Las estrategias de afrontamiento utilizadas durante la pandemia del COVID-19 podrían explicar por qué unas personas experimentan mayores niveles de ansiedad y depresión que otras. Una muestra de 747 sujetos completó un cuestionario adhoc sobre hábitos durante la pandemia, el cuestionario del afrontamiento del estrés (CAE) centrado en el COVID-19; y los Inventarios de ansiedad (BAI) y depresión (BDI-IA) de Beck. Se registraron altos porcentajes de la muestra con niveles moderados y graves de ansiedad (45.38%) y depresión (32.13%), siendo superiores en mujeres. El modelo de regresión explicó el 30.8% y el 33.5% de la varianza en ansiedad y depresión respectivamente, siendo mayor la capacidad predictiva en mujeres que en hombres. Las estrategias de afrontamiento pasivo conformaron el modelo de regresión, siendo la autofocalización negativa la que mostró mayor capacidad predictiva tanto en ansiedad (R2 = 0.204) como en depresión (R2 = 0.215). Los resultados evidencian la necesidad de trabajar en incrementar la percepción de control de la situación, promoviendo estrategias de afrontamiento activas. Palabras clave: Emergencia; estrés; género; hábitos; pandemia.